Analysing vegetation cover of an area using established Green Index from Satellite Image - S, Manna; S, Mitra (International Journal of Computer Sciences and Engineering, 2019)
In present day scenario decrease in tree count or vegetative area is one of the major challenges to humanity. Identification of vegetative area and analysing the density of forest cover is one of the fields in remote sensing. Manually detecting the vegetation change effectively and accurately is quite time consuming. Hence comes the need of automated system which identifies area of forest cover, analyses its density and makes a comparison of its vegetative cover of an area over a certain time period. This paper establishes a parameter ‘Green Index’ to identify forest cover of an area. Satellite images are used to monitor any change. The spectral index NDVI (Normalized Difference Vegetation Index) is used to calculate green index of an area from satellite image. Histogram is plotted for different wavelengths (Red, Green, and Blue) versus different area (Forest, Desert, Sea and Snow area) to compare its green index.